Pelatihan Pembuatan Instalasi Hidroponik Mini Untuk Green House SD Bustanul Ulum Semen Padang Mendukung Program Asean Eco School 2020 - Desmarita Leni; Ruzita Sumiati; Adriansyah Adriansyah; Fardinal Fardinal; Jana Hafiza (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
SD Bustanul Ulum Semen Padang is located on Jl. Komp. Kuranji Batu Busuk Hydropower Kel.Lambung bukit kec. Pauh. Training given to teachers and students of SD Bustanul Ulum (BU) Semen Padang to make a mini hydroponic installation so that the existing green house can be organized and can develop plant seeds. As well as fostering the spirit of elementary school students bu to care more about the environment early. And provide knowledge about vegetable cultivation techniques, organic nurseries with hydroponic systems. Training on making hydroponic installations in the school green house teaches school students can cultivate a variety of plants to green the school sd BU Semen Padang. This program has been started since SD BU Semen Padang obtained an independent adiwiyata tropy at the national level and SD BU strives to improve the quality as a school that cares & cultures the environment for the proposal of Asean Eco School candidates from 21 provinces throughout Indonesia. Solutions offered to solve the problems that occur in SD Bustanul Ulum Semen Padang by providing mini hydroponic equipment assistance, training in assembling mini hydroponic installations and providing knowledge about using the correct hydroponic equipment so that the needs of plant nurseries in the green house of SD Bustanul Ulum Semen Padang can help the stability of greening the school